Effect of thermal pretreatments and cooking characteristics on physicochemical, rheological, and sensorial properties of food products based on cassava (Manihot esculenta Crantz). (4th October 2017) - Vega, Oscar; Carvajal, Luz Marina; Rodríguez, Faber; Marín, María Clara; Ramírez, Cristian; Simpson, Ricardo; Valdenegro, Mónika
Abstract: The aim of this work was to develop, characterize and standardize four food products using cassava: cassava cake, dessert, ice cream, and a milk drink, evaluating the effect of cooking on quality. The methodology included the food handling and processing of the cassava products and the performance of textural, rheological, nutritional, and sensory studies of the final products. The sensory panel favorably rated all foods. All of the products developed received high acceptability scores from the sensory panel. The apparent viscosity of the beverage increased over time, whereas the firmness of the ice cream bar and the firmness of the cassava cake did not significantly change during the observation period. The sensory analysis identified typical descriptors for each food. We concluded that cassava is a functional raw material, which combined with other additives, conserves their properties, and is ideal for preparing bakery products, flavored beverages, and ice cream. Practical applications: In this study, four different food processing alternatives by cassava were performed by the community support of rural women from the village of Lebanon Township Andes, west of the Department of Antioquia in Colombia. Process lines were established for foods made from cassava, for its standardization and incorporation of processing of tubers in diet of the indigenous population of Colombia. Subsequent to this stage, the food obtained was evaluated physicochemical, nutritional, and sensory. It is important that research projects support the rural entrepreneurial units to strengthen the food security in the region as well as to improve the quality of life through the commercialization of new products. This research may contribute with strategy for the development and utilization of cassava and cassava products that can provide incentives for farmers, crop vendors and food processors to increase their incomes, and it can also provide food security for households producing and consuming this foods.